The Development of Microsoft Excel-Based Computer Simulation to Improve the Studentâs Concept Understanding on Buffer Solutions - Khaldun, Ibnu; Hanum, Latifah; Habibati, Habibati (Proceedings of the UR International Conference on Educational Sciences, 2018)
The utilization of computer as a learning media is very important especially in this sophisticated era. With the help of computer, the learning process will run more effectively and efficiently. But in fact, chemistry learning has not been utilizing the IT facilities widely as a medium of learning. The purpose of this study was to determine the feasibility of computer-based simulation learning media on the subject of buffer solution in terms of validity and effectiveness of Microsoft Excel-based computer simulation that was developed to improve the studentsâ conceptual understanding. Media development method in this research used ADDIE model which includes Analysis, Design, Development, Implementation and Evaluation. The results showed that computer-based learning media simulation of Microsoft Excel on buffer solution in terms of validity was feasible to use. The percentage of media worthiness was 81.00% according to the material experts and 81.57% of the media experts. Microsoft Excel-based computer simulation media developed effectively against conceptual understanding of buffer material. The studentsâ conceptual comprehension increased with N-gain value 89.17%.